Extent of Educational Partnerships in the Implementation of Alternative Learning System in Northern Samar Division: Inputs for Enhancing Program Delivery - Luna, Jerome Tonog (International Journal of Research in Interdisciplinary Studies, 2025)
The study investigates the extent and effectiveness of educational partnerships in the implementation of the Alternative Learning System (ALS) in Northern Samar Division, Philippines. Framed by Republic Act No. 11510 and DepEd Order No. 024, s. 2022, the research examines how collaborative engagements among local government units (LGUs), non-governmental organizations (NGOs), private entities, and community stakeholders contribute to ALS program delivery. Employing a qualitative-descriptive research design, data were gathered through semi-structured interviews, small group discussions, and document analysis involving ALS implementers, learners, and partner representatives across selected island and mainland municipalities. Findings revealed that partnerships are instrumental in providing learning venues, instructional materials, livelihood and skills training, and psychosocial support—essential elements in ensuring accessible and inclusive ALS delivery. However, the study also identified challenges such as the lack of formalized agreements, sustainability issues, and inconsistent stakeholder engagement. The study concludes that while educational partnerships significantly enhance ALS implementation, strategic improvements in coordination, policy support, and capacity-building are crucial. Recommendations include institutionalizing partnership mechanisms, strengthening monitoring systems, and fostering inclusive stakeholder participation to ensure sustained and effective ALS delivery, particularly in geographically isolated and disadvantaged communities.